A proteção da dignidade da pessoa humana como causa justificadora para uma intervenção internacional institucional - Grisi Neto, Afonso (2018)
During the last two decades, the matter of States’ internal conflicts has been becoming important as well as their adverse consequences, which come from the survival conditions of their populations, bringing the discussion of a theme which, for a long time, has been deserving the attention of International Relations and International Law scholars and which consists of the pursuit of a system composed of principles and rules meant to promote, in the broadest way possible, the protection and defence of dignity and rights of the human person. Associated to this matter and to its corollary, there is place for one of the most burning and controversial themes of politics and international relations, which is the admissibility of interventions practiced by States and International Organizations in States in which situations of flagrant contempt of the minimal conditions of human dignity can be verified. The discussion around an intervention undertaken on the conditions already mentioned before is inserted in a broader debate involving two significant issues about international relations, which are State’s sovereignty and legitimacy of humanitarian interventions. The classical concept of sovereignty states that it means absolute power of the State over people and things within its territory and, in this sense, an intervention in a particular State, even if aimed towards humanitarian ends, would represent an affront to its sovereignty. During the last two decades, however, by the proliferation of internal conflicts in several States, discussion has arisen on whether the State, in the name of its sovereignty, had the right to inflict suffering and, in many cases, even to kill its population. In 2001, the United Nations (UN), upon the study of a specialized commission, released the “Responsibility to Protect” doctrine. According to this doctrine, the State is responsible for giving protection and assistance to its population and if, somehow, it does not comply with its obligation or is incapable of doing so, the international community will supply this State’s deficiency, intervening in order to reorganize it, restoring peace and stability to its population. According to the “Responsibility to Protect” doctrine, State’s sovereignty, formerly seen as a State’s “right”, becomes its “responsibility” to protect its population. As it is seen, the “Responsibility to Protect” doctrine has a double objective: 1) it grants the first responsibility to protect its population to the respective State; 2) it enables, additionally, the UN’s intervention in this State, as an institution representing the international community. The alluded doctrine comes to support a mechanism from the UN’s Letter, which forbids the intervention practiced in a State, unilaterally, by another State or by groups of States, without a warrant from that entity. Therefore, it is through the sense of dignity as a human person’s essence, as his or her intrinsic value, that it is developed, in the present work, the idea that every aggression to this fundamental value, coming from the own State, coming from radical groups established in it, is framed as an international illegal act. In this sense, the UN, with all its flaws and imperfections, is still the representative body of international community. Thus, the “Responsibility to Protect” doctrine can be considered a significant step towards the search for means and instruments, which legitimize and justify humanitarian interventions